The Influence of Brand Image and Price on the Purchase Decision of Minyakita Cooking Oil (Case Study in Sukajaya Village, Cibitung) - Anggraini, Vita Liana Puspita; Eka Putri Yudilestari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The palm oil industry in Indonesia is one of the industries with the highest export value in the world in the agricultural sector for the past ten years. One of the products made from palm oil raw materials is cooking oil. In Indonesia, the most commonly used cooking oil is Palm Cooking Oil (Refined Bleached Deodourised Olein/RDBO). According to data from the National Food Agency (Bapanas), in 2023 the average Indonesian person will consume 9.56 kilograms of cooking oil/capita/year. MinyaKita is a brand of cooking oil under the ownership of the Directorate General of Domestic Trade of the Ministry of Home Affairs which is a solution to the high price of cooking oil. According to data from the Ministry of Trade, the price of Minyakita brand cooking oil increased throughout last year, reaching a national average of IDR 17,200 per liter in December 2024. This price increase certainly affects purchasing decisions. This study aims to determine the effect of brand image and price on purchasing decisions for MinyaKita cooking oil in Sukajaya Village, Cibitung. The research used in the study is quantitative research. The sampling method used was purposive sampling with 100 respondents from the community who use MinyaKita cooking oil in Sukajaya Village. Data analysis in this study used multiple linear regression processed with the help of SPSS 27 for Windows software. The results of the study showed that brand image and price had a positive and significant effect on the Purchase Decision of MinyaKita Cooking Oil in Sukajaya Village, Cibitung